Mechanical optimization of plate-screw interfaces in variable-angle locking systems: a parametric study - Lin, Chen-Chiang; Wang, Shun-Ping; Lin, Kun-Jhih; Hu, Ming-Hsien (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionVariable-angle locking systems offer increased surgical flexibility by permitting off-axis screw insertion, with some designs allowing angulation up to 15°. However, clinical challenges such as screw loosening and insufficient mechanical stability data persist. This study aims to evaluate the impact of different plate hole design parameters on the locking strength of plate-screw head interface under various screw insertion angles, providing insights to optimize VALS performance in fracture fixation.MethodsVariable-angle locking system with Point-Loading Thread-In mechanism was designed for investigation. Variations in locking hole design were evaluated based on slot size (1.3 mm vs. 1.5 mm), number of thread columns (three vs. four), and cone angle (20° vs. 22°). A total of eight distinct design groups were included for analysis. The screws, inserted at different inclinations (0°–15°), and locked at 0.8 Nm were subjected to a cantilever load-to-failure test. Ultimate bending moment at the screw-head interface and failure mode of the locking mechanism were determined.ResultsThe results exhibited a decrease in bending strength with increasing screw angulation in both three- and four-thread designs, with all groups exceeding 1 Nm at 0° but falling below 1 Nm at 15°. The highest bending moment was 1.46 Nm in the three-thread-column design at 0°, compared with 1.32 Nm in the four-thread-column design. At 15° screw angulation, the highest moments were 0.92 Nm and 0.90 Nm for the three-thread and four-thread designs, respectively. The plate hole with 1.3 mm slot, three thread column and 22° cone design showed higher bending moment than all other designs at each insertion angles.DiscussionPlate hole design—specifically slot size, thread number, and cone angle—significantly influences locking strength. The optimal design (3 slots, 1.3 mm, 22°) offers superior mechanical stability, guiding device optimization.